Conjugation invariants in word Hopf algebras. - Neset Deniz Turgay (2012)
We calculate a basis for the free submodule formed by the invariants in the Leibniz-Hopf algebra under the Hopf algebra conjugation operation. We also give bases for the submodules of conjugation invariants in the dual Leibniz- Hopf algebra and in the mod p reductions of both the Leibniz-Hopf algebra and its dual.